Service marketing development - Nurmakhanovа, Гульнара; Vasilievа, Мария (Рroblems of engineering and professional education, 2023)
Active development of sphere of services became the important characteristic of the past century. Today the tertiary sector of economy brings the powerful contibution to increase in well-being of many countries. We are considered and analyzed approaches of vauious authors to interpretation of terms "service" of its model, necessity of cosideration of these concepts for marketing activity is proved